Identifikasi Bahaya, Penilaian Risiko dan Upaya Pengendaliannya: Studi Kasus di Departmen Papercore PT. XYZ - Febiana Puspita Jatiningtyas; Kriswanto Widiawan (Jurnal Titra, 2023)
In this increasingly advanced era, almost all products are sold using plastic-based packaging. One of these plastic packaging products is produced at PT. XYZ. In supporting the production process, PT. XYZ needs raw material in the form of the paper core which is produced by PT. XYZ in the Papercore Department. This study aims to find out what potential hazards exist in the new department, then how much risk assessment is obtained, and what controls can be carried out. The method used in this study is HIRARC assisted by observation and interviews with production workers and other company parties. In practice, this research will focus on identifying existing potential hazards, assessing hazard risks, and proposing risk controls. There were 15 potential hazards with a high and medium risk rating, consisting of 9 mechanical categories, 5 chemical categories, and 1 ergonomic category. The proposed risk controls include technical engineering, administrative controls, and the use of PPE. From the existing risk controls, a reduction in the potential hazard risk rating was obtained to 15 hazards with a low-risk rating.